2022
DOI: 10.1371/journal.pgph.0001330
|View full text |Cite|
|
Sign up to set email alerts
|

Social vulnerability during the COVID-19 pandemic in Peru

Abstract: The COVID-19 pandemic has demanded governments and diverse organizations to work on strategies to prepare and help communities. Increasing recognition of the importance of identifying vulnerable populations has raised a demand for better tools. One of these tools is the Social Vulnerability Index (SVI). The SVI was created in 2011 to identify and plan assistance for socially vulnerable populations during hazardous events, by providing disaster management personnel information to target specific areas. We aimed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The residents of the Coast region have 3999 greater probabilities of perceiving a lower vulnerability of family health compared with the Jungle region's residents. Similarly, a study of a Peruvian population showed that the provinces with high and very high social vulnerability indices are mostly located in rural areas, predominantly in the provinces in the country's south and highlands 29 . In addition, the United Nations International Children's Emergency Fund (UNICEF) points out that people in urban areas perceive less vulnerability compared to people in rural areas, who have been more affected by the abrupt loss of family income and difficulty in accessing essential goods and services, such as health, social protection programs, and economic support, availability of nutritious food, lack of sanitary infrastructure and access to water, as well as the lack of connectivity options and distance education 30…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…The residents of the Coast region have 3999 greater probabilities of perceiving a lower vulnerability of family health compared with the Jungle region's residents. Similarly, a study of a Peruvian population showed that the provinces with high and very high social vulnerability indices are mostly located in rural areas, predominantly in the provinces in the country's south and highlands 29 . In addition, the United Nations International Children's Emergency Fund (UNICEF) points out that people in urban areas perceive less vulnerability compared to people in rural areas, who have been more affected by the abrupt loss of family income and difficulty in accessing essential goods and services, such as health, social protection programs, and economic support, availability of nutritious food, lack of sanitary infrastructure and access to water, as well as the lack of connectivity options and distance education 30…”
Section: Discussionmentioning
confidence: 97%
“…In turn, a review by Pinquart and Teubert showed that parents of children with chronic diseases experienced higher levels of stress, anxiety, and depression, which could affect the overall perception of family health. 29 In addition, siblings of children with chronic diseases were also found to face emotional challenges and may experience the country's south and highlands. 29 In addition, the United Nations International Children's Emergency Fund (UNICEF) points out that people in urban areas perceive less vulnerability compared to people in rural areas, who have been more affected by the abrupt loss of family income and difficulty in accessing essential goods and services, such as health, social protection programs, and economic support, availability of nutritious food, lack of sanitary infrastructure and access to water, as well as the lack of connectivity options and distance education.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations